Highly efficient NIR-II photothermal therapy amplified ROS oxide breast tumor therapy by mesoporous gallium-enriched platinum nanomedicine - Ying, Yunfei; Su, Yonghui; Wang, Ao; Li, Tingting; Zhuang, Hongjun; Li, Siyaqi; Liu, Xiaolong; Lin, Kecan; Wang, Peiyuan; Zhang, Fuxing (Materials today bio, 2025)
Rational design and exploitation of nanomaterials with superior treatment properties for suitable indications is a way out to relieve cost constraint of therapy and solve the unsatisfactory efficacy for cancer patients. In this work, in order solve the current bottleneck problems of photothermal therapy (PTT) with longer light excitation as well as synergistic eactive oxygen species (ROS) storm mediating via mental element catalyst without toxic side effects. We have proposed a one-step method to produce mesoporous PtGa bimetallic composition with surface modification of PEG2000 (PtGaP) for the first time. Specifically, it can effectively concentrate at tumor tissues via the mesoporous nanostructure. Owing to the strong absorption in NIR-II region (1000–1700 nm) from Pt and Fenton-like catalyst of Ga, the ROS storm is efficaciously mediated. Remarkably, under safer NIR-II (1064 nm) laser irradiation, both in vitro and in vivo studies confirm that our bimetallic mesoporous nanomedicine effectively prevents tumor growth through synergistic PTT and oxidative therapy (OXT). Given its high bio-safety performance, we can conclude that the PtGaP has strong biocompatibility and holds great prospect in clinic translation. [Display omitted]